Prevalence, Risk Factors, and Antimicrobial Resistance Profile of Respiratory Pathogens Isolated From Suckling Beef Calves to Reprocessing at the Feedlot: A Longitudinal Study - Nobrega, Diego; Andres-Lasheras, Sara; Zaheer, Rahat; McAllister, Tim; Homerosky, Elizabeth; Anholt, R. Michele; Dorin, Craig (Frontiers in Veterinary Science, 2021)
Here we investigated the prevalence and risk factors for presence of Histophilus somni, Mannheimia haemolytica, Mycoplasma bovis and Pasteurella multocida in the respiratory tract of calves from the spring processing to the reprocessing at feedlots. Additionally, we characterized, phenotypically and genotypically, the antimicrobial resistance (AMR) profile of the four species. Calves from 22 cow-calf operations were enrolled in the study (n = 30 calves per operation) and sampled by deep nasopharyngeal swabs at three time points: spring processing, weaning or induction into feedlots, and at reprocessing at the feedlot. Isolates were tested for susceptibility using the minimum inhibitory concentration (MIC) test against commonly administered antimicrobials. Additionally, a subset of isolates underwent whole-genome sequencing to infer presence of AMR genes and resistance determinants. Among studied pathogens, P. multocida was the most prevalent species, regardless of time point, followed by M. haemolytica, M. bovis, and H. somni. For M. bovis, a sharp increase in prevalence was detected at the reprocessing sampling, whereas for P. multocida, an increase in prevalence was observed at the weaning / induction sampling. Comingling and co-location of feedlots were not associated with prevalence of any respiratory pathogen. In terms of AMR, resistance against macrolides was prevalent in M. bovis, with most isolates resistant against tildipirosin, tilmicosin and tylosin. In general, there was limited evidence to support an increase in resistance rates of respiratory bacteria from the spring processing to reprocessing at feedlots, with the exception of florfenicol resistance in M. bovis, which increased at reprocessing. Metaphylactic administration of tetracyclines at feedlot induction was not associated with the MIC of tetracyclines in any respiratory bacteria. Conversely, there were clear associations between the parenteral use of macrolides as metaphylaxis at the feedlot induction, and increased MIC against macrolides in P. multocida, M. haemolytica and H. somni. Overall, the AMR phenotypes were corroborated by presence of AMR genes. We hypothesize that the administration of macrolides such as tulathromycin at feedlot induction contributes to historical changes in macrolides MIC data of respiratory bacteria of beef cattle.